2013
DOI: 10.1016/j.wneu.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from War: A Comprehensive Review of the Published Experiences of the Iranian Neurosurgeons During the Iraq-Iran Conflict and Review of the Related Literature

Abstract: Abstract:Background: The present study was aimed to review the articles published by Iranian neurosurgeons regarding their experiences during Iraq-Iran 8-year conflict and compare it with reports from other conflicts. Methods: The relevant papers and studies, published up to December 2011, were searched from three databases including MEDLINE, and two Iranian databases of Iran Medex and Scientific Information Database with the keywords Iran, Iraq, conflict, battle, war, traumatic aneurysm (TA), post-traumatic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…The lesion was explored and removed by excision under local anesthesia. The histological examination of the aneurysm showed no vessel wall layer and it was diagnosed as a pseudoaneurysm ( Figure 3A-C (22). After that report, we found one TICA (9), and one TECA on STA 21; and a series of 11 patients with 13 TECAs reported by Cox et al which was dismissed in that study (12).…”
Section: Casementioning
confidence: 74%
See 2 more Smart Citations
“…The lesion was explored and removed by excision under local anesthesia. The histological examination of the aneurysm showed no vessel wall layer and it was diagnosed as a pseudoaneurysm ( Figure 3A-C (22). After that report, we found one TICA (9), and one TECA on STA 21; and a series of 11 patients with 13 TECAs reported by Cox et al which was dismissed in that study (12).…”
Section: Casementioning
confidence: 74%
“…The limitation of the first case reported here was not to use CT-angiography or DSA for detecting any possible vascular injury. Doppler ultrasonography (DU) and/or CT-angiography may be sufficient for detecting STA aneurysm (19,22). In the second case, CTangiography definitely revealed a pseudoaneurysm of the STA.…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…Brandvold et al, in long-term analysis of Israeli survivors found that 48% had retained in-driven intracranial bone and further questioned the need to aggressively remove all penetrating fragments (8) . The Iran-Iraq war also led to a wealth of published data, including reports on the causes of infections and the vascular complications of penetrating head injuries (7,9,10) . Closed head injury data from bomb blasts in the Lebanon conflict, and later from the Iraq conflict emphasize the complexity of blast injuries, which combine the elements of both penetrating and blast effects (11) .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, some reports have appeared wherein wartime brain wounds have been treated by minimal brain debridement with little or no attention to tight dural closure. Many of these reports claimed that debridement would also affect partially devitalized adjacent brain tissue, and might have led to additional neurologic deficits or lesser degree of recovery of functions (8)(9)(10)12) . The aim of this paper is to present the experience with the management of a group of patients with warrelated penetrating brain injuries during the Syrian conflict in early 2013.…”
Section: Introductionmentioning
confidence: 99%